Growth and productivity of Bt cotton (Gossypium hirsutum) underrow spacing and nitrogen doses - SINGH, HASANDEEP; SINGH, GURINDER; LAL, MOHINDER (The Indian Journal of Agricultural Sciences, 2023)
A study was carried out at the Campus for Research and Advanced Studies, Dhablan, within the Department of Agriculture at Khalsa College, Patiala, Punjab during the rainy (kharif) season of 2019. The study encompassed 3 distinct row spacing levels i.e. 40 cm, 60 cm, and 80 cm combined with 4 nitrogen application levels, viz. 25% of the recommended nitrogen dose (RDN), 50% RDN, 100% RDN (equivalent to 90 kg/ha) and an elevated 125% RDN. Results indicate that both row spacing and nitrogen levels play a noteworthy role in influencing the growth traits, yield related attributes and overall yield of Bt cotton. Specifically, a row spacing of 80 cm exhibited superior performance in terms of growth characteristics such as leaf area per plant, no. of monopodial branches per plant, and no. of sympodial branches per plant. This choice of row spacing subsequently contributed to the enhancement of yield attributing characters, including single boll weight, the number of picked bolls per plant, seed weight per boll and seed weight per plant. But row spacing of 60 cm is required to produce a higher seed cotton yield, ginning percentage, biological yield, harvest index and economic parameters. Among nitrogen levels, 125% RDN kg/ha recorded significantly higher growth, yield attributing parameters, yield, and economic parameters followed by 25% and 50% RDN kg/ha but on par with 100% RDN kg/ha. Therefore, drawing from the findings of this study, it can be deduced that the row spacing of 60 cm with 100% RDN kg/ha is required for getting higher growth and productivity of Bt cotton. These findings contributes to enhance the resource efficient practices, maximizes yield and promotes sustainability. Optimized nitrogen levels benefit both crop and soil health, reducing the impact of excess usage and insufficient nitrogen on crop while boosting productivity for long-term farm viability, all while considering the crucial aspect of row spacing.